Using radio programming to reach young adolescents with gender and sexual health information in a low-income urban setting in Kenya - Beatrice W. Maina; Vivian Nyakangi; Michelle Mbuthia; Caroline W. Kabiru (Reproductive Health)
Abstract Background Radio programs have been used to broadcast health information across Africa and beyond. However, there has been limited focus on radio programming targeting young adolescents (aged 10 – 14) with gender and sexual and reproductive health (SRH) information. An increasing body of evidence indicates a need to provide young individuals with accurate and easily accessible gender and SRH information to equip them to make well-informed choices about their SRH. Methods We developed an engaging and educative seven-session radio show, which featured skits and guest speakers. A local radio station in Kenya broadcasted the show as a weekly episode over seven consecutive weeks. The main objective of the show was to improve young adolescents’ SRH knowledge, foster equitable gender norms, and enhance parent-adolescent relationships. To gauge perceptions about the radio program, we conducted in-depth interviews with a purposeful sample of 17 parents and 20 adolescents aged 12—14 years living in an informal settlement in Nairobi and who had participated in (or listened in on) at least three of the sessions; the radio manager and program presenter. Results Both parents and adolescents indicated that they felt more connected to each other after listening to the program and this enhanced communication, especially on SRH issues. Resulting from the radio program, both adolescents and parents expressed greater awareness of gender and adolescent SRH issues, which were rarely discussed in detail in open forums in their context prior to the radio program. They recommended that such radio programs run regularly as they provide a platform where sensitive issues about adolescent health can be shared and discussed openly, allowing for both adolescent and community participation. Conclusions Radio programming was perceived as a good platform for knowledge transfer and discussions about gender norms and SRH among young adolescents. However, messages should be designed to resonate with a diverse audience, as radio listenership will not only be limited to the target population.